Trends and composition of government expenditures on agriculture in Ghana, 1960-2015 - Benin, Samuel (International Food Policy Research Institute, 2019)
When African leaders launched the Comprehensive Africa Agricultural Development Programme (CAADP) in Maputo in 2003, they committed to spend 10 percent of their national expenditure budget on the agricultural sector. This commitment, popularly known as the Maputo Declaration, was designed in pursuit of a 6 percent agricultural growth rate each year. The African Union (AU) developed a guidance note on the measure to use to track progress in the commitment on government agriculture expenditure (GAE). The measure is based on the classification of the functions of government (COFOG), and the definition of GAE as the expenses of the government sector on agriculture—crops, livestock, forestry, and fishing and hunting (AU-NEPAD 2015). Specifically, the measure is the share of GAE in government total expenditure (GTE), which is GAE*100/GTE. Two recent agricultural public expenditure reviews (agPERs) conducted in Ghana show expenditure shares that are overestimated for measuring progress toward the Maputo 10 percent target, ranging from 6.5 to 21.2 percent in 2001–2011 (MOFA 2013) and from 5.8 to 7.5 percent in 2012–2015 (MOFA 2017). This is because the studies used concepts like “COFOG-plus” or “enhanced-COFOG” to include expenditures that are not meant to be included according to the AU guidance note. One example of this discrepancy is that the studies included government expenditures on feeder roads in GAE, although feeder roads promote socioeconomic development of entire rural communities and not just the agricultural sector. Also, expenditures of the Ghana Cocoa Board (Cocobod) were included in GAE, even though Cocobod, although responsible for the management and development of the cocoa subsector, is not part of the government sector. It is a public corporation that engages in market-based production activities financed entirely by the cocoa subsector that it serves, and there is no transfer from taxpayers through the Cocobod to the entire agricultural sector.2 Along with these inconsistencies with the official AU guidance note, the estimates and analyses in the two agPER studies mask the relatively low government expenditure in the noncocoa subsector, and may undermine efforts to boost provision of public goods and services in this subsector, which accounts for about 90 percent of Ghana’s agricultural gross domestic product (GDP). The cocoa subsector accounts for the remaining 10 percent of agricultural GDP.